1996
DOI: 10.1038/383185a0
|View full text |Cite
|
Sign up to set email alerts
|

Transcription activation in cells lacking TAFIIs

Abstract: The general transcription factor TFIID is composed of the TATA-box-binding protein (TBP) and a set of TBP-associated factors (TAFIIs). In vitro, TAFIIs are required for activated transcription, and have been proposed to be obligatory targets of transcriptional activator proteins (activators)2. The function of TAFIIs has not been investigated systematically in vivo. A Saccharomyces cerevisiae TAFII complex (yTAFII complex) has been identified that shares functional and structural similarities with higher eukary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
241
2
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 230 publications
(264 citation statements)
references
References 24 publications
20
241
2
1
Order By: Relevance
“…TFIID plays a role in transducing the activation signal from upstream regulatory proteins to the basal machinery by directly interacting with transcriptional activators (Verrijzer and Tjian, 1996). Consistent with an important role for CCG1/TAF II 250 in G1 progression, a temperature-sensitive mutation in yTAF II 145, the homolog of CCG1/TAF II 250 in budding yeast, also causes cell cycle arrest in G1 at the restrictive temperature (Moqtaderi et al, 1996;Walker et al, 1996).…”
Section: Introductionmentioning
confidence: 94%
“…TFIID plays a role in transducing the activation signal from upstream regulatory proteins to the basal machinery by directly interacting with transcriptional activators (Verrijzer and Tjian, 1996). Consistent with an important role for CCG1/TAF II 250 in G1 progression, a temperature-sensitive mutation in yTAF II 145, the homolog of CCG1/TAF II 250 in budding yeast, also causes cell cycle arrest in G1 at the restrictive temperature (Moqtaderi et al, 1996;Walker et al, 1996).…”
Section: Introductionmentioning
confidence: 94%
“…Cells were collected by centrifugation, washed and frozen on dry ice. RNA was isolated by glass bead disruption, as described in previous publications Walker et al, 1996). Northern blotting was performed (Sambrook et al, 1989;Apone et al, 1996) using the entire coding region of CLB2.…”
Section: Northern Blottingmentioning
confidence: 99%
“…Specificity of suppression. taf145-2 (Walker et al, 1996), tsm1/taf170 (Ray et al, 1991), taf17-2 and taf17-3 (Apone et al, 1998) mutant strains were transformed with the plasmids indicated in the centre of each panel. Ten-fold serial dilutions of saturated cultures were spotted onto plates and grown at 23uC or 37uC (taf145-2) or 37uC taf170/tsm1, taf17-2 and taf17-3).…”
Section: Taf68 and Cdc28 Mutations Are Synthetically Lethal In Combinmentioning
confidence: 99%
See 2 more Smart Citations